The Multi-Etnik Community Integration Model in Bali: Pholosphical Base and Proto Multiculturalism in Balinese Society - Suastika, I Nengah; Sudika Mangku, Dewa Gede; Rai Yuliartini, Ni Putu; Lasmawan, I Wayan (International Journal of Criminology and Sociology, 2022)
Ethnic conflicts that occurred in various regions in Indonesia did not occur in Bali Province. There is a set of values that are used as the basis for building unity in diversity. These values are crossed and cut, so they can be used as shared values and unifying values. This research aims at describing the integration of multicultural society’s shared place of worship and the integration of multicultural society in traditional organizations in Bali Province. This study used a qualitative approach, which described the integration model of Balinese multicultural society based on etic and emic perspectives. The research instruments used were interview guidelines, observation guidelines, and documentation study guidelines. The integration model of multicultural communities in Bali is developed on religious activities through the construction of a shared place of worship in one area, with temples and musholla. In the social life, A multi-ethnic community established common traditional organizations such as Pecalang and Subak which protect all people. The establishment of multicultural society integration in Bali is due to the shared values that are believed by the multi-ethnic community and the existence of traditional cross-cutting organizations. The shared values are used as guidelines for living together in religious, social and cultural activities.